Resident Doctors’ Attitude and Perception about Antibiotics usage, and Resistance in a Tertiary Care Hospital, in Lahore (Journal of Fatima Jinnah Medical University, 2018)
The objective of this study was to assess attitude of resident doctors towards antibiotic prescribing patterns, and their perception of antibiotic resistance. This study was conducted in Shalamar teaching hospital Lahore.100 resident doctors were enrolled but 86 residents responded to the questionnaire. 78(90.6%) residents agreed that antibiotics are over prescribed nationally. Only 41(47.6%) residents were satisfied with their current knowledge of antibiotics. 59(68.6%) residents considered antibiotic resistance as a problem. This study provides helpful information for designing strategies to optimize antibiotic usage and to prevent antibiotic resistance.